Multivariate Analysis Approach to Select Parents for Hybridization Aiming at Yield Improvement in Cucumber (Cucumis sativus L.) (Journal of Environmental Science and Natural Resources, 2015)
Twenty two genotypes of cucumber (Cucumis sativus L.) were evaluated using D2 and principal component analysis (PCA). The genotypes were collected from Plant Genetic Resources Centre (PGRC) of Bangladesh Agricultural Research Institute (BARI), Gazipur , Agro-G, & Lal Teer seed company. The study was undertaken at Sher-e-Bangla Agricultural University Farm, Dhaka during March 2010 to October 2010 to select suitable donor parents for improved breeding of cucumber. Principal component analysis (PCA) revealed that the first two axes accounted for 67.39% of the total variation among the fourteen characters studied. As per cluster analysis, the genotypes were grouped into four clusters consisting 5, 3, 8 and 6 genotypes which revealed that there exist considerable diversity among the genotypes. Highest intra-cluster distance was found in cluster ?I and lowest in cluster ?V. Among four clusters, the highest inter-cluster distance was observed between cluster ?I and cluster ? and lowest between cluster I and cluster ?V. Considering all of the characters studied, the Serena, BD-4305, BD-4256, CU937F1 and BD-4309 were selected for future breeding programme.DOI: http://dx.doi.org/10.3329/jesnr.v6i1.22036 J. Environ. Sci. & Natural Resources, 6(1): 33-36 2013